MEMBEKALI USAHA MANDIRI LULUSAN PRODI D3 KEPERAWATAN CURUP MELALUI PELATIHAN AKUPRESUR - Yanti Sutriyanti; Sri Haryani; Chandra Buana; Roestam Aji (Politeknik Negeri Sriwijaya, 2023)
The uptake of graduates of Curup D3 Nursing Study Program has reached 76% in various service institutions both at home and abroad. There are 24% who are not yet working because they do not get support from their parents to work outside the area, most are unemployed and a small number are continuing their Bachelor of Nursing education in 2022. The purpose of community service is to provide acupressure training so that graduates are able to add skills independently that can be compared when providing nursing care when dealing with clients in the community. Community service method for graduates who have not worked as many as 25 people. The implementation of the training is divided into 2 stages, namely the stage of providing knowledge and the stage of implementing direct practice to clients. Training by resource persons who are health workers, a nurse and an observant midwife and acupressure therapy practitioners in the community. The results of the training of 25 participants increased the basic knowledge and skills of acupressure, the mean pre knowledge was 10.60 and the mean post was 20.40. Each graduate performs basic acupressure practices which are evaluated by the resource person.